2005
DOI: 10.1007/s00122-005-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic affinities in Arachis section Arachis (Fabaceae): molecular and cytogenetic evidence

Abstract: Section Arachis is the largest of nine sections in the genus Arachis and includes domesticated peanut, A. hypogaea L. Most species are diploids (x = 10) with two tetraploids and a few aneuploids. Three genome types have been recognized in this section (A, B and D), but the genomes are not well characterized and relationships of several newly described species are uncertain. To clarify genomic relationships in section Arachis, cytogenetic information and molecular data from amplified fragment length polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
85
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 30 publications
7
85
2
1
Order By: Relevance
“…However, dot blot hybridization challenges those results, since A. glandulifera DNA showed less genomic affinity with A. batizocoi than with any other species of the B genome group and even than the species included in A genome group. Considering the B genome taxa, the fact that A. glandulifera DNA showed strongest hybridization with A. williamsi followed by A. ipaensis, resembles the results obtained with the analysis of the plastid trnT-L region, in which A. glandulifera clustered in a sister clade to that formed by A. batizocoi and some other B genome species (Tallury et al, 2005). Moreover, in that analysis A. williamsi was joined by a polytomy to the cluster of D genome species, whereas A. ipaensis was included (although with a low bootstrap value) into the base of the clade of the B genome species.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…However, dot blot hybridization challenges those results, since A. glandulifera DNA showed less genomic affinity with A. batizocoi than with any other species of the B genome group and even than the species included in A genome group. Considering the B genome taxa, the fact that A. glandulifera DNA showed strongest hybridization with A. williamsi followed by A. ipaensis, resembles the results obtained with the analysis of the plastid trnT-L region, in which A. glandulifera clustered in a sister clade to that formed by A. batizocoi and some other B genome species (Tallury et al, 2005). Moreover, in that analysis A. williamsi was joined by a polytomy to the cluster of D genome species, whereas A. ipaensis was included (although with a low bootstrap value) into the base of the clade of the B genome species.…”
Section: Discussionsupporting
confidence: 76%
“…Molecular markers have shown that A. glandulifera is more distantly related to the A genome species than to the B genome species Tallury et al, 2005). Within the latter group, A. batizocoi appears as the species with higher genome affinity with A. glandulifera.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations